The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1029/2019gc008332
|View full text |Cite
|
Sign up to set email alerts
|

Trace Elements and Sr, Nd Isotope Compositions of Surface Sediments in the Indian Ocean: An Evaluation of Sources and Processes for Sediment Transport and Dispersal

Abstract: To decipher sediment provenance, understand dispersal pattern and its controlling factors in the Indian Ocean, we have studied major and trace element abundances and isotope compositions of Sr (87Sr/86Sr) and Nd (εNd) in silicate fractions of 38 surface sediment samples collected at ~1.5° interval from India (~10°N) to Antarctica (~70°S). The 87Sr/86Sr ratio and εNd vary from 0.70527 and 0.1 near Crozet Island to 0.77854 and −34.8 near Antarctica, respectively. Higher 87Sr/86Sr ratio and lower εNd near Antarct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 115 publications
0
6
0
Order By: Relevance
“…Oliver and Boyet [89] suggested that Ce an , as well as the enrichment of HREE relative to LREE, could be masked due to elevated contents of terrigenous material. This situation is particularly true, as regards the clay minerals and fine grain quartz, often depleted together with REE [90,91]. Bau and Dulski [92] proposed a binary diagram, which provides a test of whether the calculated negative Ce an was real, or masked by positive La an (Figure 20).…”
Section: Discussionmentioning
confidence: 99%
“…Oliver and Boyet [89] suggested that Ce an , as well as the enrichment of HREE relative to LREE, could be masked due to elevated contents of terrigenous material. This situation is particularly true, as regards the clay minerals and fine grain quartz, often depleted together with REE [90,91]. Bau and Dulski [92] proposed a binary diagram, which provides a test of whether the calculated negative Ce an was real, or masked by positive La an (Figure 20).…”
Section: Discussionmentioning
confidence: 99%
“…Sr and REEs followed by Nd were separated from the dissolved samples using the columns that contain AG 50W‐X8 (200–400 μm) resin and Eichrom LNspecTM (50–100 μm) resin respectively. Detailed column separation procedure has been discussed elsewhere (Giri et al, 2021; W. Rahaman, Singh, Sinha, & Tandon, 2009; Samal, Srivastava, & Rahaman, 2021; Subha Anand et al, 2019).…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Detailed column separation procedure has been discussed elsewhere (Giri et al, 2021;W. Rahaman, Singh, Sinha, & Tandon, 2009;Samal, Srivastava, & Rahaman, 2021;Subha Anand et al, 2019).…”
Section: Sampling and Analytical Methodsmentioning
confidence: 99%
“…Concerning deep circulation, the North Atlantic Deep Water (NADW) (Sverdrup et al, 1942), transported from the Northern Hemisphere high latitudes by the Deep Western Boundary Current, occupies the region between the 2000 and 3000 m isobaths. The NADW flows between two northwardflowing branches of the Circumpolar Water (i.e., Upper and Lower Circumpolar Deep Water).…”
Section: Ocean Circulationmentioning
confidence: 99%